Targeted Delivery of BMS-1166 for Enhanced Breast Cancer Immunotherapy - Yu Z; Zhou Z; Zhao Y (International Journal of Nanomedicine)
Zhecheng Yu,1– 4 Zeya Zhou,1– 4 Yunqi Zhao1– 4 1College of Science, Mathematics and Technology, Wenzhou-Kean University, Wenzhou, Zhejiang, People’s Republic of China; 2Wenzhou Municipal Key Laboratory for Applied Biomedical and Biopharmaceutical Informatics, Wenzhou-Kean University, Wenzhou, Zhejiang, People’s Republic of China; 3Zhejiang Bioinformatics International Science and Technology Cooperation Center, Wenzhou-Kean University, Wenzhou, Zhejiang, People’s Republic of China; 4Dorothy and George Hennings College of Science, Mathematics and Technology, Kean University, Union, NJ, USACorrespondence: Yunqi Zhao, College of Science, Mathematics and Technology, Wenzhou-Kean University, Wenzhou, Zhejiang, People’s Republic of China, Tel +86 577 5587 0000, Fax +86 577 5587 0101, Email yuzhao@kean.eduBackground: Cancer immunotherapy has achieved great success in breast cancer treatment in recent years. The Programmed Death-1 (PD-1) /Programmed Death-Ligand 1 (PD-L1) immune checkpoint pathway is among the most studied. BMS-1166, a PD-L1 inhibitor, can interfere with PD-1 and PD-L1 interaction. Transferrin Receptor 1 is a transmembrane glycoprotein overexpressed in various cancer cells, including breast cancer, and can specifically interact with the T7 (HAIYPRH) peptide.Purpose: This study hypothesized that BMS-1166-loaded T7-modified poly(ethylene glycol)-poly(ϵ-caprolactone) (PEG-PCL) polymeric micelles (BMS-T7) could block PD-L1 interaction with PD-1, serving as a targeted immunotherapy for TfR1-positive breast cancer.Methods: BMS-1166 was encapsulated in T7-PEG-PCL micelle. Particle size and zeta potential were determined by dynamic light scattering. Particle morphology was studied by transmission electron microscopy. The particles were characterized by Fourier transform infrared, thermogravimetric analysis, and differential scanning calorimetry. Drug encapsulation efficiency, loading degree, and release profile were examined by high-performance liquid chromatography. Human breast cancer MDA-MB-231 was used to test the cytotoxicity. Flow cytometry and immunofluorescence imaging were used to study the PD-L1 inhibition in cell surface and exosomes. MDA-MB-231 and Jurkat co-culture studied T-cell activation and apoptosis.Results: The particle size of the empty and drug-loaded micelles showed a size distribution with an average diameter of 54.62 ± 2.28 nm and 60.22 ± 2.56 nm, respectively. The encapsulation efficiency of BMS-T7 was 83.89 ± 5.59%. The release half-life of drug-loaded micelles was 48h. The IC50 of BMS-1166 was 28.77 μM in MDA-MB-231 cells. In addition, the BMS-T7 showed a better inhibitory effect on PD-L1 expression in breast cancer cells and exosomes than the naked drug. The formulation significantly restored T-cell function compared to the BMS-1166 treatment.Conclusion: These results provide preliminary evidence indicating that BMS-T7 may have the potential to deliver drugs to breast cancer cells via active targeting and hold great promise in cancer immunotherapy drug delivery applications.Keywords: PD-L1, BMS-1166, immunotherapy, breast cancer, micelles